2020
DOI: 10.1136/bmj.m1403
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19: testing times

Abstract: Rapid near patient testing for both current and past infections is urgently required

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
205
0
26

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(238 citation statements)
references
References 10 publications
7
205
0
26
Order By: Relevance
“…The World Health Organization (WHO) has declared Covid-19 a pandemic, triggering various travel restrictions, border control, contact tracing, quarantine and social distancing measures in many countries (2). Despite these interventions, Covid-19 continues to spread, with 2 million cases reported globally (3), and even in countries with welldeveloped public health systems and aggressive implementation of measures (4). For instance, Singapore which reported its first imported case on 23 rd Jan 2020 and the first local transmission on 4 February 2020 (5,6), has seen a ten-fold increase in cumulative cases in the past 25 days (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization (WHO) has declared Covid-19 a pandemic, triggering various travel restrictions, border control, contact tracing, quarantine and social distancing measures in many countries (2). Despite these interventions, Covid-19 continues to spread, with 2 million cases reported globally (3), and even in countries with welldeveloped public health systems and aggressive implementation of measures (4). For instance, Singapore which reported its first imported case on 23 rd Jan 2020 and the first local transmission on 4 February 2020 (5,6), has seen a ten-fold increase in cumulative cases in the past 25 days (7).…”
Section: Introductionmentioning
confidence: 99%
“…(5). Diagnostic testing is recognized as a rate-limiting step, and there is a global need to ramp up laboratory capacity, in both well-developed and low-income countries (4,12). This is worsened by the possibility that asymptomatic individuals in the community could transmit infection, hence increasing the need to screen healthy individuals or those with mild symptoms (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Effective large-scale detection of the population is a favorable measure to identify the patients infected with COVID-19 [29,30]. Nevertheless, results from our study showed that the majority of the COVID-19 patients carry low viral loads in the upper respiratory tract, but a small population of them carry high viral loads.…”
Section: Discussionmentioning
confidence: 69%
“…Due to the high virus spread rate it is necessary tests for diagnosis that are quick and precise [5]. The precise diagnosis in patients with Covid-19 permit they receive due medical attention, furthermore placing these patients in isolation will decrease the disease spread [5].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high virus spread rate it is necessary tests for diagnosis that are quick and precise [5]. The precise diagnosis in patients with Covid-19 permit they receive due medical attention, furthermore placing these patients in isolation will decrease the disease spread [5]. The test standard to the Covid-19 diagnosis is the quantitative polymerase chain reaction (qPCR), however this exam needs several hours to confirm positivity [20].…”
Section: Introductionmentioning
confidence: 99%